2010
DOI: 10.1007/s11434-010-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated compounds in milk, milk powder and yoghurt purchased from markets in China

Abstract: The exposure to perfluorinated compounds (PFCs) through the diet for humans is of great concern. Among the diet, dairy products are in great demand. This paper reports the study on the levels of 9 perfluorinated acids and 2 fluorotelomer acids in milk, milk powder and yoghurt purchased from Chinese markets from 2008 to 2009. The analytes were quantitated by high performance liquid chromatography/electrospray tandem mass spectrometry (HPLC-ESI-MS/MS). In milk samples, perfluoroheptanoic acid (PFHpA) and perfluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
5
21
0
Order By: Relevance
“…The ADI PFOS for the general Xinjiang adult population (≥18 years old) was 0.0318 ng/kg/day, which exceeded ADI PFOA (0.0211 ng/kg/day). The calculated intakes in the present study are similar to the reports of Wang et al [21] and Ericson et al [42], but lower than those reported in a Norwegian study [20]. The different estimated intakes can be related to the differences in background levels of contaminants for milk, consumption data of various regions, and data treatment on non-detects.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The ADI PFOS for the general Xinjiang adult population (≥18 years old) was 0.0318 ng/kg/day, which exceeded ADI PFOA (0.0211 ng/kg/day). The calculated intakes in the present study are similar to the reports of Wang et al [21] and Ericson et al [42], but lower than those reported in a Norwegian study [20]. The different estimated intakes can be related to the differences in background levels of contaminants for milk, consumption data of various regions, and data treatment on non-detects.…”
Section: Resultssupporting
confidence: 83%
“…The analytical method used in this study was based on the method reported by Wang et al [21], with some modifications. Briefly, PFOS and PFOA were extracted by ultrasonic extraction with methanol (MeOH) and then purified using solid-phase extraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methanol, sodium hydroxide in methanol solutions, acetonitrile, and ethyl acetate are usually employed for the extraction of polar or relatively polar contaminants such as PFCs [26,27,[34][35][36][37] and BPA-related compounds [38][39][40] in milk, yoghurt, canned fish and cereal baby food samples. Frequently, mixture of solvents such as dichloromethane with cyclohexane, acetonitrile-hexane, methanol-hexane-methyl tert-butyl ether, hexane-acetone and tetrahydrofuran-water are also employed, for instance some of them for the extraction of phthalates [41,42] and BPA [43].…”
Section: Sample Preparationmentioning
confidence: 99%
“…The mechanisms and pathways by which PFOS and PFOA are incorporated into the human body are not well understood. However, research has indicated that potential sources of human exposure to PFOS and PFOA included food [11][12][13], drinking water [14], and respiration [11,15].…”
mentioning
confidence: 99%